A case report of arthroscopic treatment of a retro-patellar GCTTS causing anterior knee pain. (April 2023) - Diri, Doried; Alasaad, Hakam; Mhana, Sedra Abou Ali; Ibrahim, Jaber
Abstract: Introduction and importance: Giant cell tumor of tendon sheath (GCTTS) is a common soft tissue tumor in hands and feet; however, it is rare in knee joints. Case presentation: We present a case of a 52-year-old female who had a retropatellar tendon giant cell tumor (GCT) in the right knee, causing vague anterior knee pain. Clinical discussion: Anterior knee pain is a challenging complaint in orthopedics due to the multiple causative reasons, the combination of several complex etiologies, and the lack of clear guidelines for an effective treatment. Conclusion: This case report aims to shed light on unlikely pathologies in complex cases. GCTTS is a rare lesion to affect the retropatellar region. However, we must keep it in mind when dealing with challenging anterior vague knee pain complaints. A comprehensive examination is essential; surgical experience and extended follow-up are mandatory for avoiding complications. Highlights: Conservational entity in orthopedics "anterior knee pain" A rare benign tumor with an uncommon location and presentation The arthroscopic treatment No recurrence at 9 months follow up with a successful outcome